Vesicular Approach Review on Nanocarriers bearing Curcumin and Applications - Upadhyay, Prashant; Singh, Deepak; Upadhyay, Sukirti (Recent Advances in Drug Delivery and Formulation, 2022)
Phytoconstituents have been used to treat a variety of human diseases for a long time, but their use in pharmaceuticals is limited because of their low aqueous solubility. Researchers have created vesicular systems to address many of the issues associated with the bioavailability and therapeutic efficacy of poorly water-soluble drugs and target the drug to the desired location in the body. Several vesicular nanocarrier systems have been developed. Review contrasts various vesicular drug delivery systems, including liposomes, sphingosomes, emulsomes, niosomes, ethosomes, virosomes, phytosomes, aquasomes, proniosomes, transferosomes, and pharmacosomes. Vesicular drug delivery technologies have sparked a scientific revolution, leading to the creation of innovative dosage forms. The present review focuses on the preparation, characterization, drug release, current market scenarios, and future trends of nanocarriers. A variety of novel drug delivery systems have arisen, involving different routes of administration to achieve safe and targeted drug delivery. This review aims to illustrate the applications, advantages, and disadvantages of the vesicular approach based on nanocarriers bearing curcumin which is widely used in gene delivery, tumor-targeting to the brain, oral formulations, and helps resolve various problems associated with drug stability and permeability issues.
Keywords: phytosomes